Coexistence of Hereditary Hemorrhagic Telangiectasia and Moyamoya Disease: A Case Report Highlighting a Potential Genetic Synergy - Liu S; Meng L; Wan Y; Liu S; Shi L (The Application of Clinical Genetics)
Shengyang Liu,1,2,* Linghui Meng,1,* YuZhu Wan,1,2 Shanfeng Liu,3 Li Shi1,2 1Department of Otolaryngology-Head and Neck Surgery, Shandong Provincial ENT Hospital, Shandong University, Jinan, Shandong, People’s Republic of China; 2Shandong Provincial Key Medical and Health Discipline of Allergy, Shandong Second Provincial General Hospital, Jinan, Shandong, People’s Republic of China; 3Department of Radiology, Shandong Second Provincial General Hospital, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Shi, Department of Otolaryngology-Head and Neck Surgery, Shandong Provincial ENT Hospital, Shandong University, Duanxing West Road, Jinan, Shandong, 250000, People’s Republic of China, Tel +86 531 83086279, Fax +86 531 87980304, Email shili126@sina.comAbstract: Hereditary hemorrhagic telangiectasia (HHT) coexisting with moyamoya disease (MMD) is exceptionally rare. We report the first case of a 45-year-old female harboring two genetic variants implicated in vascular disease: a pathogenic mutation in ACVRL1 (c.1231C>T, p.Arg411Trp) and a novel variant of uncertain significance in RNF213 (c.13685C>T, p.Pro4562Leu). This case is remarkable for the concurrent manifestation of HHT-associated peripheral telangiectasia and MMD-characteristic intracranial arterial stenosis, suggesting a possible synergistic interaction between variants affecting distinct vascular signaling pathways. These findings offer new insights into the genetic mechanisms underlying complex hereditary vascular disorders and emphasize the importance of comprehensive genetic testing in diagnosing atypical vascular phenotypes.Keywords: hereditary hemorrhagic telangiectasia (HHT), moyamoya disease (MMD), gene variants, synergistic interaction